The Pantyliner Ekstrak Kunyit (Curcuma longa L.) sebagai Indikator Alami untuk Deteksi Ketuban Pecah Dini - Hipni, Rubiati; Isnaniah, Isnaniah; Olfah, Yustiana (Jurnal Skala Kesehatan, 2026)
Premature rupture of membranes (PROM) is one of the causes of obstetric complications that impact increased maternal and fetal morbidity and mortality. PROM diagnosis generally uses litmus paper, but this method still has the weakness of subjectivity of the results. This study aims to develop pantyliners with a natural indicator based on turmeric extract (Curcuma longa L.) as an alternative to detect PROM. Purely experimental research was conducted in the laboratory and Sultan Suriansyah Hospital, Banjarmasin. Phytochemical tests showed that turmeric extract positively contained alkaloids, flavonoids, saponins, and quinones that act as antioxidants, anti-inflammatories, antimicrobials, and immunomodulators. GC-MS tests showed the dominant compounds were Ar-turmerone (29.38%) and Alpha-turmerone (22.79%), with supporting compounds in the form of vanillin, aromatic phenolics, and fatty acid esters. Turmeric extract immobilized on pantyliners showed significant color changes when dripped with amniotic fluid (reddish brown), vaginal secretions (bright yellow), and urine (yellow). Statistical tests showed a significant effect (p<0.005) between changes in pantyliner color and the diagnosis of PROM. These results demonstrate that turmeric extract contains antioxidant, anti-inflammatory, antimicrobial, and immunomodulatory properties and has the potential to be used as an environmentally friendly natural indicator for early detection of PROM.